2017
DOI: 10.1142/s2010326317500071
|View full text |Cite
|
Sign up to set email alerts
|

Thinning and conditioning of the circular unitary ensemble

Abstract: We apply the operation of random independent thinning on the eigenvalues of n × n Haar distributed unitary random matrices. We study gap probabilities for the thinned eigenvalues, and we study the statistics of the eigenvalues of random unitary matrices which are conditioned such that there are no thinned eigenvalues on a given arc of the unit circle. Various probabilistic quantities can be expressed in terms of Toeplitz determinants and orthogonal polynomials on the unit circle, and we use these expressions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…A corollary of the determinantal structure is that the gap probability EN,2false(0;J;xaex;ξfalse) (the extra argument ξ on top of the arguments used in can be thought of as a thinning parameter: each eigenvalue is deleted independently with probability (1ξ) and therefore 0<ξ1 (see, eg, the recent works as well as the pioneering paper), which has the operator‐theoretic form EN,2false(0;J;xaex;ξfalse)false)=trueprefixdetfalse(double-struckIξKN,Jfalse),where double-struckI is the identity operator and KN,J is the integral operator with the kernel acting on L2false(Jfalse). As a consequence, the large N expansion of for J=(0,s/4N)—referred to as a hard edge scaling—can be deduced from knowledge of the corresponding large N asymptotics of .…”
Section: Functional Form Of Optimal Correction Term For Complex Wishamentioning
confidence: 99%
“…A corollary of the determinantal structure is that the gap probability EN,2false(0;J;xaex;ξfalse) (the extra argument ξ on top of the arguments used in can be thought of as a thinning parameter: each eigenvalue is deleted independently with probability (1ξ) and therefore 0<ξ1 (see, eg, the recent works as well as the pioneering paper), which has the operator‐theoretic form EN,2false(0;J;xaex;ξfalse)false)=trueprefixdetfalse(double-struckIξKN,Jfalse),where double-struckI is the identity operator and KN,J is the integral operator with the kernel acting on L2false(Jfalse). As a consequence, the large N expansion of for J=(0,s/4N)—referred to as a hard edge scaling—can be deduced from knowledge of the corresponding large N asymptotics of .…”
Section: Functional Form Of Optimal Correction Term For Complex Wishamentioning
confidence: 99%
“…Recently, the thinning and conditioning models have appeared in many situations. For example, gap and conditional probabilities for the thinned unitary ensembles are derived in [6,14]; the asymptotic behavior of mesoscopic fluctuations in the thinned CUE is studied in [3]; the transition between the Tracy-Widom distribution and the Weibull distribution as the probability ω ↓ 0 is considered in [10]; see also [11] for another interesting transition. A nice application in the study of the Riemann zeros can be found in [9].…”
Section: Painlevé XXXIV Universalitymentioning
confidence: 99%
“…A celebrated toy example is the behaviour near 0 of the squared singular values of Ginibre matrices, also known as the Laguerre Unitary Ensemble [25]. Other examples include non-intersecting squared Bessel paths [17], and the conditional Circular Unitary Ensemble near the edges [5].…”
Section: Introductionmentioning
confidence: 99%